Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ñ€Ð°Ð·Ð»Ð¸Ñ‡Ð½Ñ‹Ñ… Ð°Ð½Ð¸Ð¾Ð½Ð¾Ð² Ð½Ð° Ð¿Ð¾ÑÑ‚Ð³Ð¸Ð¿ÐµÑ€Ñ‚Ð¾Ð½Ð¸Ñ‡ÐµÑÐºÐ¸Ð¹ Ð»Ð¸Ð·Ð¸Ñ ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² - Olejnik, O. A.; Abu Al Asal, F.; Ramazanov, V. V.; Bondarenko, V. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2006)
We have studied the effect of variations with different anionic content of the rehydration media on cell sensitivity to posthypertonic lysis (PHL). We have shown that the level of erythrocytes’ posthypertonic damage is determined by entering in a cell of penetrating anions at the moment of rehydration. It was noted that cytoskeleton participated in the regulation of erythrocytes resistance to PHL.